Limits of External Dependence for Development in Africa - Davies, Emmanuel Opuene; Wali, Naomi; Taylor, Tamunosaki (NIU Journal of Social Sciences, 2020)
Most African Countries and their leaders have been facing the problem of development of their various states. This situation has led many third world countries, particularly African countries to source for foreign assistance – financially and otherwise to solve their development problems since efforts made internally have not helped matters. Before the independence of most African countries, external aid was insignificant. Thus, one of the objectives of this paper is to examine the contributions and limits of external aid in Africa’s development efforts. The paper also assessed the impact of external dependence in Africa’s development. The paper adopts the historical description method of analysis. The sources of data include text, journal, internet, library research and works of other scholars related to the study. The study used the dependency theory as the framework for analysis. Findings show that African countries had depended on external sources, particularly from the developed countries for their developmental needs from the early period of their independence and the conditions given by the developed countries had brought about some limitations for Africa’s development. The paper, therefore, recommends that African countries must device an alternative sustainable development strategy that are less anchored on foreign sources for implementation, embark on serious regional economic integration and diversify their economies. Keywords: Limit, External, Foreign aid, Dependence, sources, Development, Nigeria, Africa.